THE ROLE OF THE PRINCIPAL OF MADRASAH IN IMPROVING THE SENSE OF NATIONALISM AND TOLERANCE IN REJECTING RADICALISM AT MTs AL HUDA PANGKALAN SUSU - Muhammad Ikhsan Ritonga (Journal of Educational Science Learning and Research, 2024)
The many problems of radicalism that are currently developing are demanded by the role of madrasahs to fight the emerging radicalism. As the head of the madrasah to avoid radicalism especially in madrasahs, a sense of nationalism and tolerance are needed. This is what drives the research in this madrasah so that we can see how nationalism and tolerance are needed by students and how the madrasah increases the sense of nationalism and tolerance and how the head of the madrasah changes the radicalism of Al Huda Pangkalan Susu. This study uses quantitative research. Therefore, this study is expected to be able to bring up radicalism in Madrasahs. Because with a strong sense of nationalism, radicalism will not develop anywhere. From these choices using the SPSS 2.5 application with a multiple regression formula, significant results were found, namely rejecting radicalism by fostering a sense of nationalism and tolerance. This is evidenced by the regression discussed being lower than the regression table (0.000 <0.05). While the role of the head of the madrasah in increasing the sense of nationalism and increasing in rejecting radicalism with the level of regression discussed being lower than the regression table (0.008 <0.05)